Pengaruh Penggunaan Lembar Kerja Mahasiswa (LKM) Berbasis Case Study Untuk Melatih Kemampuan Memecahkan Masalah Pada Mahasiswa - Sabila, Sefrinda Byartika; Budijastuti, Widowati; Indana, Sifak (BRILIANT: Jurnal Riset dan Konseptual, 2024)
This research aims to determine the effect of using case study-based student worksheets to train students' problem-solving skills. This research is an experimental research with a one group pre-test Â¬post-test design. The research subjects were 26 Agribusiness Animal Husbandry students, class IB, Semester 1. The research instrument is a test of student learning outcomes. Data collection techniques are carried out using tests, observation and documentation. The data analysis technique uses the non-parametric Wilcoxon statistical test. The research results showed that 26 students obtained pre-test learning outcomes of 3.4 and post-test 3.8, meaning there was an increase in student learning outcomes after the treatment, by 0.4 or 40%. The n-gain value of problem-solving skills for students as a whole was obtained on average 0.6 which is included in the medium category. There is an influence between the pre-test and post-test learning outcomes of the BSF maggot production and reproduction biotechnology course material on BSF maggot animal development structure material for IB livestock agribusiness students.